The Relationship between Managers' Budget-Oriented Behavior and Selected Attitude, Position, Size, and Performance Measures - Swieringa, Robert J.; Moncur, Robert H. (Journal of Accounting Research, 1972)
Robert J. Swieringa, Robert H. Moncur, The Relationship between Managers' Budget-Oriented Behavior and Selected Attitude, Position, Size, and Performance Measures, Journal of Accounting Research, Vol. 10, Empirical Research in Accounting: Selected Studies 1972 (1972), pp. 194-209